(3OjhGf GHf GdNjGWs - (3CMeO Hf eMeO Hf Ydj Hf jMji GdJZdHj, CHh YHO Gddg, GdeYQha HGHf GdNjGW,J (B517 (3g` s ((3eMeO eMeO eeO GdhLH GdeGdci s)
(3ChdgG (B:s
(3YJGOc Cf JTf HgG eZGQkG abOgG Tf JHGQG s
(3BNQgG (B:s
(3dbO UObJ ai fOGg GdXfhf adG cPHJ ai YdGg GdhYhO Je GdOjhGf HCSQg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B214 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B136s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs